1987
DOI: 10.1288/00005537-198709000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage‐perichondrial composite graft tympanoplasty in the treatment of posterior marginal and attic retraction pockets

Abstract: The atelectatic retraction pocket (ARP) has been implicated in the development of chronic otitis media and cholesteatoma. The ARP's tendency for persistence or recurrence despite treatment is a significant otologic problem. The purpose of this study is to define and discuss this clinical entity and the use of cartilage-perichondrium tympanoplasty as a safe and predictable method of treatment, reducing destructive complications while maintaining ear function. A retrospective analysis of 85 operated ears is pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0
4

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 22 publications
1
86
0
4
Order By: Relevance
“…Gerber et al [13] analyzed the hearing results of cartilage and fascia tympanoplasty in a frequency-specific manner and compared two groups; they observed that there was no significant difference between the groups. Levinson et al [14] reported that ABGs were reduced to 10 dB in 65% and to 20 dB in 86% of patients who underwent cartilage tympanoplasty. Dornhoffer [15] did not find any significant difference in hearing gains after cartilage-perichondrium grafting and perichondrium grafting alone.…”
Section: Discussionmentioning
confidence: 99%
“…Gerber et al [13] analyzed the hearing results of cartilage and fascia tympanoplasty in a frequency-specific manner and compared two groups; they observed that there was no significant difference between the groups. Levinson et al [14] reported that ABGs were reduced to 10 dB in 65% and to 20 dB in 86% of patients who underwent cartilage tympanoplasty. Dornhoffer [15] did not find any significant difference in hearing gains after cartilage-perichondrium grafting and perichondrium grafting alone.…”
Section: Discussionmentioning
confidence: 99%
“…Although temporal muscles show high success rates in the early postoperative period after tympanoplasty, some studies have reported a decrease in graft performance in later stages (13,14). Due to these negative results, thicker and stronger cartilage grafts are used as alternatives (13,15,16). With its rigid and thick structure, cartilage is resistant to resorption and atrophy (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…3 The use of cartilage in middle ear surgery dates back to 1959, when it was used in management of retraction pockets. 4,5 Cartilage is the material of choice with chronic Eustachian tube dysfunction due to its increased stability. 6 Heermann was the first to introduce cartilage palisade technique in 1962.…”
Section: Introductionmentioning
confidence: 99%